GROWTH AND DEVELOPMENT OF CALVES OF DIFFERENT CONSTITUTIONAL TYPES IN PASTURE CONDITIONS - U. A. Iskenderov (Journals Park Publishing, 2024)
The article presents the growth and development of young animals of different body types in pasture conditions, feed rations and live weight for them.
Keywords: Constitution, ratio, protein, rough, fine, strong.